Optimum mix of foamed concrete by using different materials - Sebeli, K. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Foamed Concrete is a special concrete which can be very useful in the construction because it is lightweight and a self compacted concrete. It is necessary here and can be cast easily into every corner of formwork especially for mass concreting. Many researches have been done in overseas show that the foamed concrete can reduce load in construction compared to normal construction. Materials used to produce foamed concrete are cheap thus it will reduce the construction cost. In Malaysia especially in Sarawak, foamed concrete is still new. Before it can be use in the constructions, a lots of study need to be done on foamed concrete. The objective of this project is to determine the optimum mix of foamed concrete using different materials which are Fly Ash (FA), Silica Fume (SF) and Calcium Carbide (CC). In this project, the mix of foamed concrete has been done on two conditions. First condition is by replacing 50% cement and second condition is by replacing the sand. Both conditions are done in two ratios 1: 1 and 1:2. Water to cement ratio is fixed 0.5 and the target wet density is 1000kg/m3 . Two tests done are Flow Table Test and Compressive Strength on 7 days and 28 days. The results from this project show different materials replaced in the foamed concrete influence the performance and quality of foamed concrete itself.